Cognição e esforço físico: a cognição de policiais é afetada pelo esforço? - Lima, Lucas Arthur Duarte de (2024)
Introduction: The performance of military police officers (PMs) involves several cognitive processes, which are particularly important when the use of a firearm is necessary. Furthermore, considering that the use of a firearm is usually preceded by a foot chase, it is important to understand whether physical effort affects the cognitive performance of PMs. Objective: To evaluate the effect of physical effort on cognitive performance in PMs. Methods: The sample consisted of 13 male PMs. Inhibitory control was assessed using a computerized version of the Stroop test before and after physical exercise. The difference in response time (RT) and accuracy between the incongruent and neutral phases were used as a measure of the Stroop effect (i.e., inhibitory control). The shooting test was performed before and after physical effort with five air pistol shots at a scored target, where the score and time to fire were recorded. The physical exercise was performed on a ~300 m circuit with obstacles that simulated a police chase, with the instruction to perform a run in the shortest possible time. The Wilcoxon test was used to compare the measures and the Spearman's rank correlation coefficient was used to correlate cognitive and shooting performance. A p<0.05 was adopted. Results: There was no significant change from pre- to post-effort in RT and accuracy for the congruent (all p>0.62), neutral (all p>0.77) or incongruent (all p>0.15) tests of the Stroop test, as well as Stroop interference when considering RT (p=0.594) or accuracy (p=0.826). Conclusion: These findings indicate that physical effort does not affect the cognitive performance of police officers. Future research should explore the influence of physical exercise performed while using duty-related equipment, the nature and duration of the effort, and the effect of physical exercise on other cognitive functions/domains, as well as include personalized controlled designs.